Perceived accessibility is an important factor in transport choice — Results from the AVENUE project. Issue 1 (March 2016) - Scheepers, C.E.; Wendel-Vos, G.C.W.; van Kempen, E.E.M.M.; de Hollander, E.L.; van Wijnen, H.J.; Maas, J.; den Hertog, F.R.J.; Staatsen, B.A.M.; Stipdonk, H.L.; Int Panis, L.L.R.; van Wesemael, P.J.V.; Schuit, A.J.
Abstract: Background: Stimulating active transport by encouraging replacement of short-distance car trips by active transport modes such as cycling or walking has become a popular policy strategy. It has been suggested that neighbourhoods, designed to facilitate healthy behaviour, can influence a person׳s behavioural choices such as transport choice. In the present study, we investigated the association between perceived accessibility of facilities and transport choice for three different trip purposes (shopping, going to public natural spaces, and going to sports facilities) in the Netherlands. Methods: An online questionnaire ( N =3663) was used to collect data concerning transport choice for the general Dutch population over a period of one calendar year starting July 2012. Logistic regression analyses were used to model the odds of cycling versus car use and to model the odds of walking versus car use. Results: When perceived accessibility by car is high, persons were less likely to use active transport modes (OR range: 0.09–0.66) and when perceived accessibility by active transport modes is high, persons were more likely to use the bicycle (OR range: 2.18–10.43) or walk (OR range: 2.97–11.22). Conclusions: Our results showed a strong association between perceived accessibility and transport choice even after adjusting for personal and environmental characteristics. Our results suggest that perceived accessibility should be taken into account when stimulating a shift from car use to cycling or walking. Highlights: Perceived accessibility was found to be strongly associated with transport choice. When perceived accessibility by car is high, persons were less likely to use active modes. Perceived accessibility should be taken into account when stimulating a mode shift.